Epigallocatechin Gallate Can Protect Mice From Acute Stress Induced by LPS While Stabilizing Gut Microbes and Serum Metabolites Levels - Ma, Yong; Liu, Gang; Tang, Muyang; Fang, Jun; Jiang, Hongmei (Frontiers in Immunology, 2021)
Epigallocatechin gallate (EGCG) has potent biological activity as well as strong antioxidant and anti-inflammatory effects. This study aims to explore the protective effect of EGCG on LPS-induced acute injury. We randomly divided 18 mice into three groups: CON, LPS, and EGCG-LPS. We gave the EGCG-LPS group gavage treatment with EGCG on day 8–15 and an intraperitoneal injection of LPS on day 16 to induce acute injury. The results showed that, compared with the LPS group, the bodyweight of the mice in the EGCG-LPS group increased significantly and effectively inhibited the morphological damage of the jejunum and liver. We measured liver tissue and found that the EGCG gavage treatment significantly inhibited the pro-inflammatory factors (TNF-α, IL-1β, IL-6, MCP-1, MIP-2, IFN-γ) and oxidation indicators (MPO, NO, ALT, and AST) levels increase. The microbiological results showed that the EGCG gavage treatment reshaped the disturbance done to the intestinal microbial community in the mice by LPS, reversed the changes in the abundance ratio of Firmicutes/Bacteroidetes, and significantly reduced the abundance of Enterobacteriales. Finally, the serum metabolomics results showed that, when compared with the LPS group, the gavage treatment of EGCG significantly increased the concentration of sphingomyelin (d17:1/17:0), sphingomyelin (d16:1/20:0), and significantly reduced the content of trans-Hexadec-2-enoyl carnitine, and so on. Therefore, we believe that EGCG can protect mice from acute stress induced by LPS while stabilizing gut microbes in general, improving the metabolism of sphingolipids, and inhibiting the content of harmful metabolites.